1971
DOI: 10.1111/j.1365-2621.1971.tb01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking on fatty acid composition of beef lipids

Abstract: Summary Paired chuck, rib, round and flank cuts were taken from carcasses of 12 Angus steers (454 kg live weight). Fatty acid composition of subcutaneous, seam (intermuscular), total intramuscular, intramuscular phospholipid and intramuscular neutral lipid fractions was determined on the raw and cooked (70°C) meat. On the basis of the fatty acids analysed (C14, C14:,1. C15, C16, C16:1, C17, C18, C18:1, C18:2, C18:3, C20:4) no significant differences were found between the lipids of the raw and cooked meat. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…In our study, cooking temperatures below 100 • C were applied, which significantly limited the extent of the Maillard reactions [4,41,56,58]. Anderson et al [59] did not observe significant differences in beef lipids, based on fatty acids analysis between raw beef and beef cooked at 70 • C. Therefore, the limited extent of the above mentioned reactions at temperatures applied in our study presumably was the reason that no significant differences were observed between samples with regard to their aroma intensity. Moreover, Clausen et al [6] did not observe a change in the free glutamate content in beef tenderloin sous vide cooked at 54 and 64 • C, which together with aroma volatile compounds delivering reactions might account for only small differences in sample flavour acceptability in the present study.…”
Section: Sensory Analysismentioning
confidence: 55%
“…In our study, cooking temperatures below 100 • C were applied, which significantly limited the extent of the Maillard reactions [4,41,56,58]. Anderson et al [59] did not observe significant differences in beef lipids, based on fatty acids analysis between raw beef and beef cooked at 70 • C. Therefore, the limited extent of the above mentioned reactions at temperatures applied in our study presumably was the reason that no significant differences were observed between samples with regard to their aroma intensity. Moreover, Clausen et al [6] did not observe a change in the free glutamate content in beef tenderloin sous vide cooked at 54 and 64 • C, which together with aroma volatile compounds delivering reactions might account for only small differences in sample flavour acceptability in the present study.…”
Section: Sensory Analysismentioning
confidence: 55%
“…Η γλουτίνη, η ο ποία είναι υδατοδιαλυτή και με την ψύξη,που ακόλουθεί τη θέρ μανση, μετατρέπεται σε ζελατίνη είναι αυτή που συγκρατεί με γάλες ποο-ότητες νερού και έχει μεγάλη ικανότητα διογκώσεως (Gustavson, 1956) . (Anderson et al, 1971" Bognär und Pückner, 1983.…”
unclassified